PENGHITUNG JUMLAH ORANG MASUK DAN KE LUAR BERBASIS IoT DILENGKAPI PENGUKUR SUHU TUBUH - Indra Pramana Yoga, I Putu; Diafari Djuni H, I Gusti Agung Komang; Pramaita, Nyoman (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
As a precaution against the spread of the Covid-19 virus in public facilities, the government requires to measure temperature and limit the number of people in order to prevent new clusters, especially in crowded centers. To reduce this problem, a prototype of the number of people entering and leaving through the IoT-based door will be made using an ultrasonic sensor HCSR-04 equipped with a body temperature meter. This system works from reading the temperature sensor value MLX90614, when the temperature is above 37oC then the door remains closed and when the temperature is below 37oC the door will open, ultrasonic sensor 1 is placed on the entrance side and ultrasonic sensor 2 is placed on the exit side, if the sensor 1 receives one input, the system will automatically add a variable number of visitors, if sensor 2 receives one input, the system will automatically reduce the variable number of visitors, and when the room is full of 10 people, the servo motor will close the door automatically, information on body temperature and total person data will be displayed on the LCD and the Blynk application and sent to the MySql webserver database in real time. The prototype system that has been made is capable of detecting body temperature and counting the number of people entering and leaving the door according to the design.